PEMEROLEHAN BAHASA PADA ANAK DENGAN RIWAYAT PERILAKU TANTRUM: ANALISIS PERKEMBANGAN KOSAKATA DAN KEMAMPUAN KOMUNIKASI - Ocktaviana, Disha (Program Studi Tadris Bahasa Indonesia, 2023)
This study aims to determine language acquisition in children aged 3 years with emotional disorders (tantrums) with a focus on the development of their vocabulary and communication skills. The research method uses a qualitative descriptive method, namely by examining the status of human groups, objects, conditions, systems of thought or current events with the aim of making systematic, factual, and accurate descriptions of the facts studied. The data obtained in this study through interviews, observation, and documentation, so as to get answers to problems in detail. The research subjects were 3 year old children with emotional disturbances (tantrums). The results of this study indicate that the acquisition of language experienced by children aged 3 years with emotional disorders (tantrums) can be qualified by the function of expressing something, desire, form of rejection, and acceptance. In children aged 3 years who experience tantrums, language acquisition and use are still developing to achieve perfection. Parents and the surrounding environment play a very important role in guiding and always providing input to achieve perfection in language acquisition.